Memento Mori: The development and validation of the Death Reflection Scale. (26th November 2018) - Yuan, Zhenyu; Baranik, Lisa E.; Sinclair, Robert R.; Sliter, Michael T.; Rand, Kevin L.; Salyers, Michelle P.
Summary: Despite its potential for advancing organizational behavior (OB) research, the topic of death awareness has been vastly understudied. Moreover, research on death awareness has predominantly focused on the anxiety‐provoking aspect of death‐related cognitions, thus overlooking the positive aspect of death awareness, death reflection . This gap is exacerbated by the lack of a valid research instrument to measure death reflection. To address this issue, we offer a systematic conceptualization of death reflection, develop the Death Reflection Scale, and assess its psychometric properties across four studies. Further, using a sample of 268 firefighters, we examine whether death reflection buffers the detrimental impact of mortality cues at work on employee well‐being and safety performance. Results provide strong support for the psychometric properties of the Death Reflection Scale. Further, moderation analysis indicates death reflection weakens the negative effect of mortality cues on firefighters' safety performance. Overall, these findings suggest the newly developed Death Reflection Scale will prove useful in future research on death‐related cognitions.